Marine Mucilage as an Outcome of Climate Change and Pollution - Yilmaz, Adem (IGI Global, 2024)
The seas are home to many living things and an excellent resource for the ecosystem. In addition, the seas are a perfect ecosystem component for both the supply of quality food for humans and the continuation of their lives. Due to the ecological and economic importance of the seas, they should be catered to consciously and in a sustainable fashion. Howbeit, the boost in human-induced problems and nature-induced problems may cause some negativities. This causes an increase in nutrients in the seas, sudden changes in water temperature, a decrease in water currents and consequently, an increase in algae and other phytoplankton. Over time, these organisms cause a substance entitled marine saliva or mucilage to cover the seas and damage the marine ecosystem. In this study, a comparative analysis of the mucilage problem, which has become a significant problem in Türkiye in recent years, is carried out. In this context, the prominent reports, the measures taken and the action plans in Türkiye are examined in detail.
Keywords: 13. Climate action; 14. Life underwater; 15. Life on land; 6. Clean water